2016
DOI: 10.1002/mc.22485
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous FABP4 increases breast cancer cell proliferation and activates the expression of fatty acid transport proteins

Abstract: Adipose tissue plays an important role in tumor progression, because it provides nutrients and adipokines to proliferating cells. Fatty acid binding protein 4 (FABP4) is a key adipokine for fatty acid transport. In metabolic pathologies, plasma levels of FABP4 are increased. However, the role of this circulating protein is unknown. Recent studies have demonstrated that FABP4 might have a role in tumor progression, but the molecular mechanisms involved are still unclear. In this study, we analysed the role of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
73
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(78 citation statements)
references
References 46 publications
4
73
1
Order By: Relevance
“…In agreement, studies in tumourbearing animals showed an increase in lipolysis and therefore an increase in the FFA release into plasma due to the hydrolysis of adipose tissue TAGs (Sakurai and Klein, 1998). Consistently, proteins that have been identified as facilitating the uptake of FAs into cells, and those involved in FA transport have also been implicated in cancer progression (Balaban et al, 2015;Guaita-Esteruelas et al, 2016). Further in support of this idea is the link between dietary FAs and breast cancer (Hsu et al, 2007).…”
Section: Circulating Free Fatty Acidsmentioning
confidence: 60%
See 2 more Smart Citations
“…In agreement, studies in tumourbearing animals showed an increase in lipolysis and therefore an increase in the FFA release into plasma due to the hydrolysis of adipose tissue TAGs (Sakurai and Klein, 1998). Consistently, proteins that have been identified as facilitating the uptake of FAs into cells, and those involved in FA transport have also been implicated in cancer progression (Balaban et al, 2015;Guaita-Esteruelas et al, 2016). Further in support of this idea is the link between dietary FAs and breast cancer (Hsu et al, 2007).…”
Section: Circulating Free Fatty Acidsmentioning
confidence: 60%
“…Several proteins such as CD36/FAT and fatty acid-binding proteins (FABPs) have been identified to facilitate the uptake of FFAs into cells. Consistent with the idea that FFAs have a role in cancer, those FA-transport proteins have also been implicated in promoting cancer progression (Balaban et al, 2015;Guaita-Esteruelas et al, 2016). The long-chain monosaturated FFA oleate has been shown to be able to stimulate the proliferation of human breast cancer cells, with PI3K having a role in this process (Hsu et al, 2007;Hardy et al, 2005).…”
Section: Circulating Free Fatty Acidsmentioning
confidence: 72%
See 1 more Smart Citation
“…In this work, we have studied the eff ect of titanium nitride and chromium disilicide nanoparticles on the expression of a subset of genes encoding different regulatory factors (IGFBP1, IGFBP2, IGFBP3, IGFBP4, IGFBP5, CD36, and PECAM1) and enzyme SNARK/NUAK2, which play an important role in various metabolic pathways and thus control the cell proliferation and apoptosis as well as angiogenesis and metastasis (Praveen Kumar et al 2014;Baxter 2015;Kim and Lee 2015;Musumeci et al 2015;Ding et al 2016;Kim et al 2016;Miller et al 2016;Phillips et al 2016;Guaita-Esteruelas et al 2017;Pascual et al 2017). For titanium dioxide nanoparticles, which are widely used in the number of applications, including cosmetic creams, toothpastes, and component of surgical implants, it has been shown that long-term exposure to these nanoparticles led to accumulation of these nanoparticles in brain, over-proliferation of glial cells and signifi cant changes in brain gene expressions as well as to neurogenic disease states in mice (Ze et al 2014;Rollerova et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…CD36 functions as a cell adhesion molecule and its inhibition impairs metastasis. Recently, it has been shown that exogenous FABP4 increases breast cancer cell proliferation and activates the expression of fatty acid transport proteins CD36 and FABP5 in MCF-7 breast cancer cells (Guaita-Esteruelas et al 2017). CD36 gene may also play some role in the pathogenesis of impaired fasting glucose/impaired glucose tolerance and type 2 diabetes (Wang et al 2012).…”
mentioning
confidence: 99%